Testing of a Classroom Facility Maintenance Monitoring System Using Alpha, Beta, and Stress Testing Methods - Jalaluddin , Afif Ibadurrahman; Kallista, Meta; Dinimaharawati, Ashri (eProceedings of Engineering, 2025)
Classroom facility maintenance at the TULT Building of Telkom University was previously managed manually through paper-based forms and control sheets, often causing delays, errors, and data loss. To overcome these inefficiencies, a web-based monitoring system was developed and evaluated using alpha, beta, and stress testing methods. Alpha testing validated all core features for three key user roles — admin (12 features), technician (10 features), and user (8 features) — with all functionality checks achieving a 100% success rate. Beta testing involved 30 respondents (2 admins, 2 technicians, and 26 users) who assessed usability through a 5-point Likert scale, resulting in an average score of 4.51 or 83.4%, categorized as “Very Good.” Stress testing simulated 300 virtual users accessing the system concurrently, yielding a stable average response time of 224 ms, a throughput of 46 requests per second, and zero recorded errors. These evaluations confirmed that the system is functionally reliable, user-friendly, and robust under high-load conditions. The testing outcomes suggest that the system is ready for operational deployment, providing significant improvements in monitoring efficiency, real-time reporting, maintenance coordination, and data accuracy. Future enhancements are recommended, such as implementing caching mechanisms, introducing load-based authentication fallback strategies, and expanding beta testing with a more diverse and larger user group to ensure system scalability and continuous improvement. Keywords— monitoring system, alpha testing, beta testing, stress testing, web application, Telkom University